Desenvolvimento de imunolipossomas anti-EGFR contendo cabazitaxel: caracterização físico-química e avaliação da atividade in vitro contra câncer de próstata - Santos, Elias da Silva (2023)
Liposomes functionalized with monoclonal antibodies appear as a specific target treatment against cancer, with sustained release, passive accumulation in the tumor environment, drug protection, in addition to allowing interaction with high affinity binding with a receptor overexpressed in tumor cells. Thus, the aim of this work was to develop anti-EGFR immunoliposomes containing cabazitaxel, perform their physicochemical characterization and evaluate in vitro efficacy in prostate cancer cell lines. The formulation that showed the best results was the one containing soy phosphatidylcholine (SPC), cholesterol (10% molar), drug:lipid ratio of 1:20, to obtain adequate particle size (136.7 ± 2.21 nm) , low polydispersity index (PDI) (0.335 ± 0.01) and high encapsulation efficiency (EE) (93.78 ± 0.71%). A 10% mole ratio of DSPE-PEG-Maleimide and 2 mg of antibody was selected for the conjugation process, showing a functionalization efficiency of 40%. It was verified in the solid state analyzes (DSC, FTIR and X-Ray Diffraction) that the drug is in an amorphous state and that the chemical groups of the drug and the antibody were present in the structure of the nanoparticle. The release study showed that 19% of the drug was released from the liposome after 72 hours of testing and that the Weibull kinetic model best applied to this formulation, while the immunoliposome released only 5% and had first-order kinetics. Regarding the in vitro biological activity, the IC50 of the PC3 (low EGFR expression) and DU145 (high EGFR expression) strains were evaluated. IC50 results were: 2.34 ± 1.34 nM for immunoliposomes; 3.48 ± 0.06 nM for the free drug and 2.98 ± 0.77 nM for the liposome in the DU145 lineage. As for PC3, the free drug showed an IC50 of 23.20 ± 1.62 nM; 35.79 ± 14.70 nM liposomes and 29.72 ± 7.72 nM immunoliposomes. Flow cytometry analysis showed that at 4 hours, both strains had low uptake, however, the immunoliposome was more internalized (15.5 ± 2.6% in DU145 and 6.2 ± 0.4% in PC3 ). At 24 hours, PC3 internalized the liposome more (93.0 ± 0.7%) and in DU145 the immunoliposome was more internalized (81.8 ± 0.4%). Thus, it was possible to develop liposomes and immunoliposomes with controlled release, pronounced in vitro biological activity at low concentrations and high degrees of cellular internalization after 24 hours.